Analysis of Soil Chemical Properties and Their Relationship with Tobacco Plant Productivity in Dry Land - Ema Rahila Azzahra; Taufik Fauzi; Suwardji; A. A. Ketut Sudharmawan (Jurnal Biologi Tropis, 2023)
Dryland is defined as land that is never flooded or submerged in water throughout the year. Indonesia has a very large area of dryland, which is 11,876,881 hectares. Generally, drylands have low fertility and thin soil layers with low organic matter content. There are several types of plants that can be cultivated in drylands, one of which is tobacco. Environmental conditions such as soil conditions (physical and chemical properties of soil) affect the production and quality of tobacco, among others, soil status. In this topic, the descriptive method was used as an approach. Data collection techniques (literature) were carried out using books, articles, and scientific journals derived from previous research. It was concluded that an increase in C-organic content, CEC, and KB increased tobacco production. Conversely, an increase in pH can adversely affect tobacco production and quality.